2017
DOI: 10.1007/s00245-017-9403-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Estimates for Multimarginal Optimal Transportation Problems with Singular Costs

Abstract: We consider some repulsive multimarginal optimal transportation problems which include, as a particular case, the Coulomb cost. We prove a regularity property of the minimizers (optimal transportation plan) from which we deduce existence and some basic regularity of a maximizer for the dual problem (Kantorovich potential). This is then applied to obtain some estimates of the cost and to the study of continuity properties.This problem is called a multimarginal optimal transportation problem and elements of Π(ρ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…In Section 4, we extend the duality results of [18,9,2] for a class of unbounded cost functions (Theorem 4.1) and in Section 5 we obtain regularity results of Kantorovich potentials (Theorem 5.2) as well as continuity of the cost functional as a function of the marginal ρ.…”
Section: 1mentioning
confidence: 86%
See 3 more Smart Citations
“…In Section 4, we extend the duality results of [18,9,2] for a class of unbounded cost functions (Theorem 4.1) and in Section 5 we obtain regularity results of Kantorovich potentials (Theorem 5.2) as well as continuity of the cost functional as a function of the marginal ρ.…”
Section: 1mentioning
confidence: 86%
“…By using arguments from physics, Seidl suggested that, at least in the case when ρ is radially symmetric, a minimizer γ in (1.1) exists and is concentrated on the graph of a map T : R 3 → R 3 , T ♯ ρ = ρ, and its iterates, i.e. γ = (Id, T, T (2) , . .…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Now we may consider two, a priori different, entropy-regularized MOT problems: the one introduced in (2.3) 4) and the problem with the reference measure chosen to be (ρm) ⊗N…”
Section: The Entropy-regularized Repulsive Costsmentioning
confidence: 99%